تأثير إضافة الفيتامينات ( A,B,C ) إلى غذاء طوائف نحل العسل المرباة في محافظة اللاذقية خلال فصل الربيع في إنتاجية الغذاء الملكي - أسعد, مينوس; مكيّس, خليل; عمران, مالك (Latakia University Journal -Biological Sciences Series, 2014)
تمّ إجراء هذه الدراسة في منحل خاص بمحافظة اللاذقية؛ لتحديد تأثير إضافة بعض الفيتامينات إلى غذاء طوائف نحل العسل المحلية في معدّل قبول الكؤيسات الشمعية والبلاستيكية المطعّمة باليرقات وفي إنتاجية الغذاء الملكي.اتضح من النتائج أنّ أفضل نسب القبول قد حققتها معاملة فيتامين Cإذ بلغت85.41 % للكؤيسات الشمعية و 75.83% للكؤيسات البلاستيكية؛ وبحسب نتائج التحليل الإحصائي فقد تفوقت معنوياً على جميع المعاملات الأخرى, بينما لم يظهر أي فرق معنوي بين المعاملة بفيتامين A والشاهد مهما كان نوع الكؤيس المستخدم. بيّنت نتائج متوسط وزن الغذاء الملكي في الكؤيس أنّ المعاملة بفيتامين C كانت 0.348 غ للكؤيس الشمعي, و0.312 غ للكؤيس البلاستيكي؛ وأظهر التحليل الإحصائي تفوق المعاملة بفيتامين C والمعاملةبفيتامينB على المعاملات الأخرى عند استخدام الكؤيس الشمعي, بينما لم يظهر أي فرق معنوي في متوسط وزن الغذاء الملكي بين نوعي الكؤيسات عند المعاملة بفيتامين A والشاهد . This study was done in special apiary (Latakia province) to define the effect of adding some vitamins on the nutrition of the local honeybee colonies at the rate of acceptation in the plastic and wax cups are grafted with larva; and in the productivity of royal jelly. The results showed that best of acceptation rate was achieved by vitamin C treatment that arrived to 85.41% in the wax cups and 75.83% in the plastic cups. According to results of the statistical analysis, it significantly surpassed upon all other treatments, whereas there wasn’t any significant difference between the treatment with vitamin Aand control, no matter what kind of cups it used. The results of average weight of the royal jelly in the cup showed that the treatment of vitamin C achieved the best value that reached to 0.348 g of the wax cups and 0.312 g of plastic cups.The statistical analysis showed superiority of the treatment vitamin C and B upon other treatments (vitamin A and control) while using the wax cups, whereas there was no significant difference in the average weight of the royal jelly between the two kinds of cups when treating with vitamin A and control.